Dominant Soil Characteristics that Effect on Available K at Smectitic Soils - DEDI NURSYAMSI; K. IDRIS; SUPIYANDI SABIHAM; AGUS SOFYAN (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2007)
Research aimed to study dominant soil characteristics that effect on available K of smectitic soils were conducted in Laboratory of Research and Soil Test, Indonesian Soil Research Institute. The soil characteristics that has been analised were soil texture (pipette), organic-C (Kjeldahl), and CEC (NH4OAc); mineralogical analyses of clay fraction (X-Ray Diffraction); K fractionation: soil soluble-K (0.0002 M CaCl2), exchangeable-K (NH4OAc), and total-K (HNO3+HClO4); and potassium sorption. The results showed that the content of soil soluble, exchangeable, non-exchangeable, and total-K was in order of Vertisols > Alfisols > Inceptisols. The percentage of soil K fraction of the soils, however, was in order of soluble-K < exchangeable-K < non-exchangeable-K. Although the soils had high content in total K but most of them were in nonexchangeable form, thus they were not available for plant growth. Soil K buffering capacity and maximum sorption were in order of Vertisols > Alfisols > Inceptisols. The bond energy constant of Vertisols, however, was similar with that of Alfisols but it was about twice with that of Inceptisols. Soil clay, organic-C, and CEC affected the availability of soil K significantly (P > 0.95). Smectite contributed significantly (P > 0.95) to soil negative charge so that it held an important role in controlling soil K buffering capacity and maximum sorption. To increase the efficiency of K fertilizer, plant species that can produce organic acid exudated from roots in high quantity can be developed in smectitic soils. The use of Na, NH4, and Fe cations need also to be considered for K management in the soils as well.